(2x-8)-3=(-1)

Simple and best practice solution for (2x-8)-3=(-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-8)-3=(-1) equation:


Simplifying
(2x + -8) + -3 = (-1)

Reorder the terms:
(-8 + 2x) + -3 = (-1)

Remove parenthesis around (-8 + 2x)
-8 + 2x + -3 = (-1)

Reorder the terms:
-8 + -3 + 2x = (-1)

Combine like terms: -8 + -3 = -11
-11 + 2x = (-1)
-11 + 2x = -1

Solving
-11 + 2x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 2x = -1 + 11

Combine like terms: -11 + 11 = 0
0 + 2x = -1 + 11
2x = -1 + 11

Combine like terms: -1 + 11 = 10
2x = 10

Divide each side by '2'.
x = 5

Simplifying
x = 5

See similar equations:

| -8(-3x+6)+6=150 | | 2x+4x+3=8 | | h=-8.75t^2+35t | | 7(x-10)+4=(-45) | | 0.8x+0.3=1.3+0.2x | | 7n-(2n+-8)= | | (2x-2y^2)dx+(12x^2-4xy)dy=0 | | -1(5x-1)+3x-3=-2 | | -5x-15=35 | | 3+30=20x+5x | | 10(x-8)=2(x-2) | | x/16=9/2 | | b=0.5(47+97) | | 11m=6+5m | | 3+30=20x+5 | | x+8=2x-62 | | 5x+12-10=55 | | 16-41=3(x-2)-4 | | -30=m-849/-3 | | 8(x-4)=-2x+48 | | 27y-3z= | | -28=-7/9y | | 24p+32+1=36p-1 | | 3x-14y= | | -(1+7v)-6(-7-x)=36 | | -529=6b+-67 | | 17-x=-69 | | 19-y=9 | | 22x-7=6x+41 | | 3[5-(y+3)]= | | 8y-3=5y+30 | | 28(q-947)=812 |

Equations solver categories